USING DRONES TO CLEAN CONTINENTAL WATER BODIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Pollution of continental water bodies has become increasingly widespread in recent decades. Plastic, construction, household and other waste is being dumped uncontrollably both near water bodies and directly into them. In addition to pollution, this often leads to more serious crisis and emergency situations such as floods, pollution of drinking and groundwater, landslides and others. This article proposes a new application of mid-range drones for monitoring pollution, the presence of unregulated landfills and transmitting information in real time. In this way, it will be possible to monitor large areas for the presence of illegally dumped waste with fewer resources. This will help to more effectively combat unregulated landfills and solve the problem in its infancy and save financial and human resources.